Implementation of the Right to Same-Sex Partnerships in the Light of the Case-Law of the European Court of Human Rights (Discourse of Law and Administration, 2026)
This article analyzes the evolution of the European Court of Human Rights’ (ECtHR) case law on the legal recognition of same-sex partnerships, with a particular focus on its impact on the Polish legal system. Starting with the historic shift in the Court’s approach—from the absence of a legal obligation for recognition (the Schalk and Kopf v. Austria case) to the finding that a complete lack of legal protection violates the Convention (the Oliari and others v. Italy case)—the text shows how this evolution has affected Poland.Key ECtHR judgments against Poland (Przybyszewska and others, Formela and others, Szypuła and others) are discussed, all of which confirm that Polish law, by not offering any form of legal recognition, violates the right to private and family life. These rulings clearly point to the systemic nature of the problem and to Poland’s positive obligation to introduce appropriate regulations. The conclusion emphasizes that the Court’s case-law functions as a “living document” that adapts to changing social realities, and Poland’s legislative inaction is inconsistent with European standards and could lead to further consequences.
Keywords: European Court of Human Rights; same-sex relationships; right to family life; right to private life